Policing Football Fans in Switzerland—A Case Study Involving Fans, Stadium Security Employees, and Police Officers. (20th November 2017) - Brechbühl, Alain; Schumacher Dimech, Annemarie; Seiler, Roland
Abstract: This article presents an analysis of the intergroup dynamics leading to violence between ultra football fans and stadium security employees and between these fans and police forces at a Swiss premier league football match. Twelve narrative interviews with these three stakeholders were conducted and analysed using Interpretative Phenomenological Analysis. The findings further support the applicability of the Elaborated Social Identity Model (ESIM) of crowd behaviour. The fans' perceptions of the out-group behaviour's illegitimacy led to a vicious circle of negative group interactions. Specifically, behaviours perceived as provocative seemed to lead to violence escalation. However, the escalation dynamics could only be understood in the context of the power dynamics between the different groups involved. We recommend more proactive forms of crowd management to facilitate positive group interactions and to avoid 'us against them' attitudes.